Los viajes de los intelectuales latinoamericanos a Europa Oriental 1947-1956 - Zourek, Michal (Ars et humanitas, 2017)
This study analyses the journeys of Latin American intellectuals to Eastern Europe in order to clarify hitherto unknown links with the region. The focal period is the decade of 1947-1956, which was characterised by the great enthusiasm leftist intellectuals felt towards the Soviet Union and the countries of the socialist block. The first part of the study presents individual written testimonies. These are put into perspective with regard to the role Latin American intellectuals played within the framework of communist propaganda and their relations with international organizations. Special attention is paid to the organization of these journeys, and to the way they contributed to the development of contacts with intellectuals in Eastern Europe. The third part of the study provides an analysis of the discourse of such texts. On the one hand, it is argued that the texts served the political needs of the time, and that their artistic value is disputable. On the other hand, the texts are remarkable testimonies of the period, one in which the connection with Eastern Europe contributed significantly to the "internationalisation" of Latin American artists. This was reflected in the increasing number of translated works of the authors, invitations to various conferences, or international prizes awarded to Latin American artists. One of the major benefits of the testimonies is the fact that they describe the contacts established between Latin American and European intellectuals. It is rather paradoxical that the first reunion of prominent Latin American figures took place in Eastern Europe. In Latin America, where leftist intellectuals were frequently subjected to persecution, such meetings would not have been possible.
Keywords: hladna vojna; intelektualci; komunizem; kulturne povezave; Latinska Amerika; pesniki; pisatelji